Ethics and Deontology in Spanish Public Universities - Rafael Delgado-Alemany; Alicia Blanco-González; Francisco Díez-Martín (MDPI AG, 2020)
The existence of ethical and deontological codes is a reality integrated in highly competitive sectors, such as the medical sector or the legal profession. Most studies on ethics and deontology focus on the way in which they are communicated and their effectiveness. However, no special interest has been paid to the existence, application and content of ethics and deontology in the university sector and its relationship with the transmission of ethical and deontological principles to students. Professionals, employees and managers who will play their role in society, perform their work in companies or develop strategic plans, are trained at universities, which must play an important role in the ethical and deontological training of future social actors. Therefore, it is necessary to respond to whether public universities have codes of ethics and whether the fact of having these codes implies a greater commitment to the inclusion of ethical values in their training programs. To this end, Spanish public universities are analyzed and the results, which are grouped by areas of knowledge, are presented. The results achieved provide useful insight for university managers concerned with implementing ethical and responsible policies.